Association of the miR‐146aC>G, miR‐149T>C, miR‐196a2T>C, and miR‐499A>G polymorphisms with gastric cancer risk and survival in the korean population. Issue 1 (21st September 2012) - Ahn, Dae Ho; Rah, HyungChul; Choi, Young‐Kook; Jeon, Young Joo; Min, Kyung Tae; Kwack, KyuBum; Hong, Sung Pyo; Hwang, Seong Gyu; Kim, Nam Keun; Angel, Joe
Abstract We investigated whether four common microRNA polymorphisms (miR‐146aC>G [rs2910164], miR‐149T>C [rs2292832], miR‐196a2T>C [rs11614913], and miR‐499A>G [rs3746444]) are associated with the susceptibility and prognosis of gastric cancer in the Korean population. The four microRNA single‐nucleotide polymorphisms (SNPs) were identified in a case–control study (461 patients; 447 controls) by polymerase chain reaction–restriction fragment length polymorphism (PCR–RFLP) analysis in the Korean population. When patients were stratified into diffuse and intestinal‐type gastric cancer groups, subjects with the miR‐499AG and AG + GG genotypes had reduced adjusted odds ratios (AORs) for diffuse‐type gastric cancer (AOR = 0.54 with 95% confidence interval [CI] = 0.31–0.97; AOR = 0.57 with 95% CI = 0.33–0.97). In the stratified analyses for gastric cancer risk, the miR‐146aGG and CG + GG genotypes were associated with increased risk of gastric cancers among the non‐smokers, whereas the miR‐149TC and TC + CC genotypes showed lower risk of gastric cancer in males. The miR‐196a2CC genotype was associated with elevated gastric cancer risk among females. For gastric cancer prognosis, intestinal‐type gastric cancer patients with miR‐146aCG + GG genotypes had significantly higher survival rates (log‐rank P = 0.030) than patients with the CC genotype, and patients with the miR‐499AA genotype had significantly increased survival rates compared to patients with the AG + GG genotypes (log‐rank P = 0.013). When miR‐146aCG + GG and miR‐499AA genotypes were combined, the survival rate of intestinal‐type gastric cancer patients was elevated (log‐rank P < 0.001). No association was found between gastric or diffuse‐type cancer prognosis and other miRNAs. Our data demonstrate that specific miRNA SNPs are associated with gastric cancer susceptibility (miR‐499A>G) and prognosis (miR‐146aC>G and miR‐499A>G) in the Korean population depending on gastric cancer type. © 2012 Wiley Periodicals, Inc.